A gap in the education of future sport scientists? - Dobiasch, M.; Aral, N.; Oppl, S (Journal of Science and Cycling, 2021)
Technological advances of the last decades have seen a vast increase in data availability in general but also in particular in the domain of sport science. Given the amount of data produced in cycling and other endurance sports, various models have been developed for (among other aspects) predicting performances based on historical data.